Intention to Be Vaccinated for COVID-19 among Italian Nurses during the Pandemic - Trabucco Aurilio, Marco (Vaccines (Basel), 2021)
Background: While the COVID-19 pandemic has spread globally, health systems are overwhelmed by both direct and indirect mortality from other treatable conditions. COVID-19 vaccination was crucial to preventing and eliminating the disease, so vaccine development for COVID-19 was fast-tracked worldwide. Despite the fact that vaccination is commonly recognized as the most effective approach, according to the World Health Organization (WHO), vaccine hesitancy is a global health issue. Methods: We conducted a cross-sectional online survey of nurses in four different regions in Italy between 20 and 28 December 2020 to obtain data on the acceptance of the upcoming COVID-19 vaccination in order to plan specific interventions to increase the rate of vaccine coverage. Results: A total of 531 out of the 5000 nurses invited completed the online questionnaire. Most of the nurses enrolled in the study (73.4%) were female. Among the nurses, 91.5% intended to accept vaccination, whereas 2.3% were opposed and 6.2% were undecided. Female sex and confidence in vaccine efficacy represent the main predictors of vaccine intention among the study population using a logistic regression model, while other factors including vaccine safety concerns (side effects) were non-significant. Conclusions: Despite the availability of a safe and effective vaccine, intention to be vaccinated was suboptimal among nurses in our sample. We also found a significant number of people undecided as to whether to accept the vaccine. Contrary to expectations, concerns about the safety of the vaccine were not found to affect the acceptance rate; nurses’ perception of vaccine efficacy and female sex were the main influencing factors on attitudes toward vaccination in our sample. Since the success of the COVID-19 immunization plan depends on the uptake rate, these findings are of great interest for public health policies. Interventions aimed at increasing employee awareness of vaccination efficacy should be promoted among nurses in order to increase the number of vaccinated people.